2003
DOI: 10.1042/bj20020449
|View full text |Cite
|
Sign up to set email alerts
|

A prothrombin activator from Bothrops erythromelas (jararaca-da-seca) snake venom: characterization and molecular cloning

Abstract: A novel prothrombin activator enzyme, which we have named 'berythractivase', was isolated from Bothrops erythromelas (jararaca-da-seca) snake venom. Berythractivase was purified by a single cation-exchange-chromatography step on a Resource S (Amersham Biosciences) column. The overall purification (31-fold) indicates that berythractivase comprises about 5% of the crude venom. It is a single-chain protein with a molecular mass of 78 kDa. SDS/PAGE of prothrombin after activation by berythractivase showed fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 64 publications
2
58
0
9
Order By: Relevance
“…Schattner et al (22) complemented the results reported by Silva et al (18) by evaluating the effects of two P-III snake venom metalloproteinases (SVMPs), berythrativase and jararhagin, isolated from B. erythromelas and B. jararaca, respectively, on HUVECs. Both SVMPs were capable of stimulating the releases of interleukin-8 (IL-8), nitric oxide, and prostacyclin (PGI 2 ) by the HUVECs.…”
Section: Overview On Bothrops Erythromelas Venomsupporting
confidence: 63%
See 2 more Smart Citations
“…Schattner et al (22) complemented the results reported by Silva et al (18) by evaluating the effects of two P-III snake venom metalloproteinases (SVMPs), berythrativase and jararhagin, isolated from B. erythromelas and B. jararaca, respectively, on HUVECs. Both SVMPs were capable of stimulating the releases of interleukin-8 (IL-8), nitric oxide, and prostacyclin (PGI 2 ) by the HUVECs.…”
Section: Overview On Bothrops Erythromelas Venomsupporting
confidence: 63%
“…In 2006, Pereira et al (31) studied berythrativase and jararhagin to complement the studies conducted by Schattner et al (22) and Silva et al (18) . Pereira et al (31) studied the differences in the biological effects of the two SVMPs on different hemostatic properties.…”
Section: Overview On Bothrops Erythromelas Venommentioning
confidence: 99%
See 1 more Smart Citation
“…SVMPs are divided into four groups (PI, II, III and IV) and subgroups that differ for the presence of additional domains on the carboxyl side of the metalloproteinase domain (4,12,17). SVMPs display several activities such as degradation of blood coagulating factors (7,30), extracellular matrix (ECM) components (4,14,23,26) and cell receptors such as the cell-surface β1-integrin receptor (18). Besides these activities, SVMPs were reported to induce apoptosis in endothelial cells (2,32).…”
Section: Introductionmentioning
confidence: 99%
“…Nessa reclassificação, a classe P-IV foi incuída na classe P-III por ser considerada como o resultado de uma modificação pós-traducional da classe P-III. SILVA et al, 2003;WANG et al, 2008), proteínas de membrana celular e à interação com receptores específicos, como integrinas de superfície de plaquetas (DE LUCA et al, 1995;YOU et al, 2006), células endoteliais (SOUZA et al, 2000;COMINNETTI et al, 2004) e fibroblastos (ZIGRINO et al, 2002), ativando ou inibindo a resposta celular. Esses efeitos podem resultar em várias alterações fisiopatológicas tais como inflamação, inibição da agregação plaquetária, apoptose e hemorragia .…”
Section: Metaloproteases De Veneno De Serpentes (Svmp)unclassified